La salud emocional desde la perspectiva de la competencia percibida - Rueda, Beatriz; Pérez-García, Ana María; Bermúdez-Moreno, José (Acción Psicológica, 2012)
Resumen La finalidad de este trabajo ha sido analizar la relación que existe entre la competencia percibida (Wallston, 1992) y los procesos de afrontamiento, así como su influencia sobre la aparición de síntomas emocionales, en una muestra de sujetos sanos. Los objetivos planteados en esta investigación fueron los siguientes: (1) confirmar que la competencia percibida promueve un afrontamiento dirigido a la solución del problema, a la vez que disminuye el afrontamiento centrado en la emoción negativa y el autoinforme de síntomas; y (2) determinar si la conexión entre la percepción de competencia y la presencia de síntomas es directa, o se halla mediada por los procesos de afrontamiento. A partir de estos resultados se pudo concluir que la creencia de competencia constituye un importante recurso psicológico, dado que reduce las consecuencias negativas del estrés, a la par que promueve un modo eficaz de afrontamiento de los problemas. Abstract The aim of the present study was to analyze the relationship between perceived competence (Wallston, 1992), coping processes, and emotional symptoms in a healthy sample. The objectives for this research were the following ones: (1) to confirm that perceived competence fosters a problem-focused coping, and reduces the emotionfocused coping and the self-reported symptoms; and (2) to establish whether the connection between perceived competence and emotional symptoms is direct or if it is mediated by coping. The sample was composed by 173 subjects, aged 17 to 67 years old and an average age of 33. The regression analyses demonstrated that perceived competence positively predicted taskfocused coping, and negatively predicted emotion-focused one as well as self-reported symptoms. Furthermore, when coping was introduced into the regression equation, only emotionfocused coping partially mediated the relationship between perceived competence and the symptoms. Neither task coping nor avoidance coping were predictors of the self-reported symptoms. We conclude that perceived competence beliefs constitute an important psychological resource as they promote an efficacious way of facing the problems and, thus, they reduce the negative consequences of stress.